2017
DOI: 10.1002/chem.201704014
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐State Energetics of Fe Complexes from an Optimally Tuned Range‐Separated Hybrid Functional

Abstract: We assess the performance of the optimally tuned range-separated hybrid (OT-RSH) functional approach in predicting the ground-state electronic configuration and spin-state energetics of complexes that can potentially exhibit multiple spin configurations. To that end, we investigate eight iron complexes: four spin-crossover complexes, for which reference data from other approximate density functionals are available, and four smaller complexes, for which reference ab initio data are available. We show that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 101 publications
(370 reference statements)
1
47
0
Order By: Relevance
“…The HSE06 functional, which applies exact exchange of 25% in the short range, has been chosen as it has been shown to perform well for phthalocyanine molecules in the gas phase [42,43,70]. In addition, for transition-metal complexes it has been shown that the spin-state energetics depend mainly on the percentage of short-range exchange, while long-range exchange and the exact value of the range-separation parameter are of less importance for this property [57,71]. To check whether this is the case also for the Pc molecules considered here, we performed additional calculations with long-range corrected functionals, elaborated below.…”
Section: Computational Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The HSE06 functional, which applies exact exchange of 25% in the short range, has been chosen as it has been shown to perform well for phthalocyanine molecules in the gas phase [42,43,70]. In addition, for transition-metal complexes it has been shown that the spin-state energetics depend mainly on the percentage of short-range exchange, while long-range exchange and the exact value of the range-separation parameter are of less importance for this property [57,71]. To check whether this is the case also for the Pc molecules considered here, we performed additional calculations with long-range corrected functionals, elaborated below.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Our gas-phase calculations are based on two methods: First, using the HSE06 functional, which has been shown to accurately describe the relative alignment of the electronic orbitals in neutral CuPc and CoPc molecules [28,43,95], and which has also been employed in the interface calculations discussed above. Second, we also perform gas-phase calculations of the CuPc and CoPc anions with an OT-RSH functional [71,80,81,96], which uses a system-dependent but nonempirical tuning of the range-separation parameter and can produce highly accurate valence-electron spectra for molecules. In particular, the excellent performance of OT-RSH has been demonstrated for metal Pcs [80,81] and for other metallorganic complexes [71,97].…”
Section: Magnetic Configurations Of Gas-phase Cupc and Copcmentioning
confidence: 99%
See 1 more Smart Citation
“…For the tuned LC-BLYP case, three different optimal pairs of parameters (α, ω) have been considered: no constant exact exchange (α=0.0) as it was predicted by analysis of fractional charges, as well as 15 and 20 % of exchange because those parameters have been proposed in earlier publications. 69,70 Taken CASPT2 as a reference, one can clearly see that the purely local BLYP drastically underestimates the energies of MLCT states but overestimates the MC states. Importantly, the energies of MC states predicted with the tuned LC-BLYP (α=0.0) almost coincide with those of BLYP, supporting the underlying assumption that at short interelectron distances the local BLYP functional dominates in Eq.…”
Section: Optimization Of the Range-separation Parametersmentioning
confidence: 96%
“…Compound spin-crossover compounds 35,37,68 . In a recent publication 69 , a value of α of 0.10-0.15 has been argued to be optimal for a series of iron spin-crossover compounds after analyzing the adiabatic energy difference between high-and low-spin states based on the comparison with the OPBE reference data 70 implying that the errors inherent to the OPBE functional may also influence this conclusion.…”
Section: Optimization Of the Range-separation Parametersmentioning
confidence: 99%